2016
DOI: 10.1007/978-3-319-34171-2_23
|View full text |Cite
|
Sign up to set email alerts
|

Improved Approximation Algorithms for Min-Cost Connectivity Augmentation Problems

Abstract: In Connectivity Augmentation problems we are given a graph H = (V, EH) and an edge set E on V , and seek a min-size edge set J ⊆ E such that H ∪ J has larger edge/node connectivity than H. In the Edge-Connectivity Augmentation problem we need to increase the edge-connectivity by 1. In the Block-Tree Augmentation problem H is connected and H ∪ S should be 2-connected. In Leaf-to-Leaf Connectivity Augmentation problems every edge in E connects minimal deficient sets. For this version we give a simple combinatori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…3 [13], and β k = O(k ln k) for k ≥ 4 [11]. We also have β ′ k = O(k 2 ln n) by [11] and the correction of Vakilian [14] to the algorithm and the analysis of [11]; see also [6].…”
Section: Rooted Subset K-connectivitymentioning
confidence: 88%
See 1 more Smart Citation
“…3 [13], and β k = O(k ln k) for k ≥ 4 [11]. We also have β ′ k = O(k 2 ln n) by [11] and the correction of Vakilian [14] to the algorithm and the analysis of [11]; see also [6].…”
Section: Rooted Subset K-connectivitymentioning
confidence: 88%
“…For various approximation algorithms for this problem see recent papers [5,4,9,6,3]. Specifically, Bansal [3] showed that if the problem of covering a γ-pliable familily achieves approximation ratio α, then (k, 3)-FGC admits approximation ratio 6 + α, thus obtaining a 22-approximation for (k, 3)-FGC.…”
Section: Capacitated K-edge Connected Spanning Subgraph (Cap-k-ecss)mentioning
confidence: 99%